Corruption in politics : a case study - Padhy, Krushna Singh, 1949- (Delhi : B.R. Pub. Corp. ; New Delhi : Distributed by D.K. Publishers' Distributors, 1986)
With reference to the Khanna Commission of Inquiry appointed by the Government of Orissa, 1967.
Includes index.
Bibliography: p. [215]-220.
Shakib
Keywords: Orissa (India). -- Khanna Commission of Inquiry; Political corruption -- India -- Bihar